2014
DOI: 10.1159/000369066
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Mouse Model for Chronic Cat Allergen-Induced Asthma

Abstract: Background: Allergic asthma is a chronic inflammatory airway disease caused by exposure to airborne allergens. In order to develop novel therapies for allergic asthma, models that are relevant to human disease are needed. Methods: Female BALB/c mice were presensitised subcutaneously with alum-adsorbed recombinant cat allergen Fel d 1, followed by intranasal challenges with cat dander extract spiked with recombinant Fel d 1 for 7 weeks. For reference, mice were presensitised and challenged with ovalbumin follow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 41 publications
1
4
0
Order By: Relevance
“…Our data indicated that low fat milk increased effectively both cell subsets in BALF comparably to OVA induced allergic airway inflammation. Consistent with the previous reports [5], [30], the pulmonary histological examination showed that OVA treated mice had various degrees of inflammation. Surprisingly, the milk challenged mice presented with more serious pulmonary inflammation as evident by increased eosinophil influx in lung and mucus hypersecretion.…”
Section: Discussionsupporting
confidence: 92%
“…Our data indicated that low fat milk increased effectively both cell subsets in BALF comparably to OVA induced allergic airway inflammation. Consistent with the previous reports [5], [30], the pulmonary histological examination showed that OVA treated mice had various degrees of inflammation. Surprisingly, the milk challenged mice presented with more serious pulmonary inflammation as evident by increased eosinophil influx in lung and mucus hypersecretion.…”
Section: Discussionsupporting
confidence: 92%
“…Lung sections stained by PAS were observed for numbers of goblet cells (stained red) in bronchiolar epithelium. A scoring system of 0–3 was used to indicate the relative number of goblet cells, with scores of 0 and 3 reflecting the same variations as described for H & E staining 38 , 39 . Lung sections stained by TRI were studied for collagen deposition (stained blue) and lung fibrosis, with scores of 0 and 3 reflecting the same variations as described for the two aforementioned staining methods.…”
Section: Methodsmentioning
confidence: 99%
“…Sensitization and Challenge Protocols. Guinea pigs were sensitized twice through intranasal instillation of 200 μg of either HDM (Greer, Lenoir, NC, USA) or CDE (Greer, Lenoir, NC, USA), prepared as described previously [12], in 300 μL of PBS (Figure 1). On the challenge days, the guinea pigs were exposed to 100 μg of either HDM or CDE twice per week for 4, 8, or 12 weeks (Figure 1) under light anaesthesia with 5% isoflurane.…”
Section: Methodsmentioning
confidence: 99%